Enhanced insulation properties of AFEP via constructing one-dimensional ZnO nanostructures - Jun Xie; Bobin Xu; Guowei Xia; Youzhi Zhang; Xiaoyu Shi; Ping Huang; Yan Li; Qing Xie (Journal of Materials Research and Technology, 2025)
Aramid fiber-reinforced epoxy resin (AFEP) composite is extensively utilized in power systems as the core material of the insulated pull rod in gas-insulated switchgear (GIS). However, owing to the significant surface inertness of aramid fiber (AF), the interface of the AFEP composite material is suboptimal, and the insulation performance is diminished, thereby limiting its further development and application. This study employs a mild hydrothermal synthesis method to create one-dimensional zinc oxide (ZnO) nanostructures on the surface of aramid fibers, enhancing the fiber surface activity. This improves the interface bonding between aramid fibers and epoxy resin, further boosting the composite material's insulation performance. The microstructure evolution of the fiber surface is verified through microscopic characterization, and the influence of different construction parameters (concentration, time) on the insulation performance. of the AFEP composite is investigated via electrical performance testing. The results demonstrate that the flashover voltage and breakdown field strength of AFEP composites increase by 54.4 % and 66.8 %, respectively. Density functional theory (DFT) calculations and molecular dynamics (MD) simulations reveal the mechanism of constructing ZnO one-dimensional nanostructures on the fiber surface to enhance the insulation performance of AFEP composites.